Isolation and identification of acetic acid producer from soil using banana stem waste as a substrate - Mohd Faizan, Jamaluddin (2013)
This research dealt with the identification of acetic acid producer (AAP) from soil mixed culture (SMC), production of acetic acid from banana stem waste (BSW) and kinetic study of the acetic acid production. 57 bacterial strains were isolated from SMC. From the isolation, 15 strains produced acetid acid. Later, only five most efficient bacterial strains were identified using biochemical test and biomolecular test. Those five strains were labeled as A1, A2, A6, A7, and A8. All isolated strains were in rod shape and the colonies size ranged was from 1.0mm to 3.0mm. A1 was identified as Bacillus cereus PG06 with 92% match, A2 as Klebsiella pneumonia ST258 with 92% match, A6 as Bacillus thuringiensis BMB171 90% match, A7 as Bacillus sp. SJ1 with 77% match and A8 as Enterobacter cloacae Y219 with 89% match. Bacillus thuringiensis BMB171 (A6) is the most productive bacteria that produced resulted in highest yield of acetic acid (up to 4.4 g/l) compared to other identified strains. Later, kinetic study was conducted using this strain. The experiment was conducted using BSW and glucose medium (as control substrate) in batch fermentation for 72 hours. The proposed kinetic model have 7 kinetic constants.